(3fXe GdOQQ aj GdMce hGdZQQs - (3Ydj Hf YHO Gdedc MSGe GdOjf GHf bGVj NGf GdbGOQj GdTGPdj GdgfOj Ke GdeOfj aGdecj, YdGA GdOjf GdTgjQ H` GdeJbj,J (B975 (3g` s ((3ecI GdeTQaI s)
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdMce SjOfG eMeO efHY GdCSQGQ hGdMce, agPG JHhjH LeYoJ ajg Hjf GdJCdjajf GdeSejf HCWhGb GdPgH ddYdGeI GdReNTQj s
(3BNQgG (B:s
(3hWjhQ aUGM JaQbI CLRGDgG Ydi LHGd GdbOS, aVegf Je GdcJGH GdeQShe HfXe GdOQQ aj GdMce hGdZQQ s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3LeY ajg cJGHj CWhGb GdPgH ddReNTQjs
(3hCWHGb GdPgH dGHf gHg Gddg GdeZQHjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs